Effects of waste waters on benthic macrofauna of sandy beaches in Todos Santos Bay - LC Jiménez-Pérez; F Molina-Peralta; E Núñez-Fernández (Ciencias Marinas, 1992)
The seasonal study of the benthic macrofauna in Todos Santos Bay shows the effects of waste waters on the benthic communities of the intertidal zone. The analysis of the data separates the fauna into two main associations: one made up of the populations that inhabit the beaches of the harbour and another made up of the populations that inhabit the municipal beaches which are less affected by anthropogenic activity. The location of an abiotic zone near the “El Gallo” stream indicates the impact of waste waters. However, the detection of some organisms of Donax gouldi (Mollusca: Bivalvia) and Scolelepis squamata (Annelida: Polychaeta) in the affected zone during winter and spring shows the beginning of a process of recuperation, indicating that the ecological damage can be eliminated if the discharge of waste waters is suspended.